2021
DOI: 10.3389/fgene.2021.802857
|View full text |Cite
|
Sign up to set email alerts
|

Differentially Expressed lncRNAs Related to the Development of Abdominal Fat in Gushi Chickens and Their Interaction Regulatory Network

Abstract: Chickens are one of the most important sources of meat worldwide, and the growth status of abdominal fat is closely related to production efficiency. Long noncoding RNAs (lncRNAs) play an important role in lipid metabolism and deposition regulation. However, research on the expression profile of lncRNAs related to the development of abdominal fat in chickens after hatching and their interaction regulatory networks is still lacking. To characterize the lncRNA expression profile during the development of chicken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…Due to their distinct flavor and nutritional value, Gushi chickens have gained significant consumer appeal. Additionally, they are frequently utilized as breeding hybrids [ 2 ]. As the demand for Gushi chickens surpasses their availability, there is a pressing need to address the challenges associated with their production process.…”
Section: Introductionmentioning
confidence: 99%
“…Due to their distinct flavor and nutritional value, Gushi chickens have gained significant consumer appeal. Additionally, they are frequently utilized as breeding hybrids [ 2 ]. As the demand for Gushi chickens surpasses their availability, there is a pressing need to address the challenges associated with their production process.…”
Section: Introductionmentioning
confidence: 99%
“…The molecular regulatory mechanism between them has been proved to play a variety of roles in many biological processes (Paraskevopoulou & Hatzigeorgiou, 2016;Yang et al, 2020;Dimitra et al, 2021). Some studies had found that the molecular regulation of miRNA and lncRNA changed during chicken obesity, and lncRNA-miRNA axis might be an important regulator of chicken abdominal fat expression (Li et al, 2015;Zhai et al, 2021). In this study, it was found that lncRNAs could target multiple miRNAs in the molecular regulatory network.…”
Section: Figurementioning
confidence: 66%
“…SNPs in the 5′ regulatory region of PPARD are strongly correlated with fat deposition traits in a local Chinese pig population ( Zhang et al, 2015 ). Some researchers have additionally proposed that PPARD interacts with lncRNA, playing a role in regulating lipid metabolism, adipocyte proliferation, and differentiation in the abdominal fat of Gushi Chickens ( Zhai et al, 2021 ). The selection signatures of QYM breed, including muscle development, fat metabolism, and reproductive performance, can be due to consumer demand for tender and flavorful yellow-feathered chicken meat.…”
Section: Discussionmentioning
confidence: 99%